FRI0390 Impaired ovarian reserve in patients affected by systemic lupus erythematosus: a case-control study. (12th June 2018) - Pacucci, V.A.; Ceccarelli, F.; D'Ambrosio, V.; Colasanti, T.; Aliberti, C.; Spinelli, F.R.; Perricone, C.; Truglia, S.; Miranda, F.; Alessandri, C.; Perrone, G.; Giancotti, A.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease showing a strong predilection for reproductive age women (female/male ratio 9:1). This is in part due to the effects exerted by sexual hormones on immune system. The term ovarian reserve has been used traditionally to describe the number and quality of oocytes in women. This is assessed by detection of FSH, AMH and Estradiol (E2) and by ultrasonographic (US) evaluation of antral follicolar bilateral count (AFC), as recommended by the Society of Reprodutive Medicine. The evaluation of AFC should be conducted in the early follicular phase of the menstrual cycle. An AFC lower than 3–4 follicles is highly specific (73%–97%) of poor ovarian function. Data from the literature about ovarian reserve in SLE showed contrasting results. Objectives: We aimed at assessing ovarian reserve in a SLE cohort, by US determination of AFC and by analysing serum levels of AMH, FSH, E2. Methods: In this case control study, we enrolled consecutive SLE patients in reproductive age (<45 years), fulfilled the 1997 ACR revised criteria, not treated by gonadotoxic chemotherapy agents. Moreover, we enrolled age-matched healthy women (HS). Clinical and laboratory data were collected in a standardised, computerised and electronically filled form, including demographics, past medical history with date of diagnosis, autoantibody profile, comorbidities, previous and concomitant treatments. We assessed the disease activity and chronic damage by using SLEDAI-2K and SDI, respectively. In order to assess AFC, patients and HS underwent to transvaginal US evaluation by a single operator (Samsung Elite USS-WS8EL4U/WR) between the 2nd and 7th day of the menstrual cycle. At the same day of the US assessment, we obtained sample of peripheral venous blood from patients and HS to evaluate FSH, AMH and E2 dosages (ELISA kit CLOUD-CLONE Corp., My Biosource, USA). Results: Nineteen SLE patients (median age 35 years, IQR 6.0; mean disease duration ±SD 12.2±7.7 months) and 8 HS were evaluated. A mean ±SD SLEDAI-2K of 2.5±1.5 was registered; 3 patients had a chronic damage (SDI=1). FSH values were significantly higher in SLE patients compared with HS ([SLE: median (IQR) 35; 6 HS: median (IQR) 3 (1.5); p=0.01]. Concerning the AFC, we found significantly lower values in SLE patients than in HS [SLE: median (IQR) 13; 11 HS: median (IQR) 22.5 (10.5); p=0.03]. The Spearman analysis demonstrated a negative correlation between AFC and BMI (r=−0.5, p=0.02), FSH (r=−0.5, p=0.04) and age (r=−0.5, p=0.02) (figure 1). AFC: antral follicolar bilateral count; BMI: body mass index; FSH: follicle-stimulating hormone Conclusions: The preservation of fertility is a crucial point in SLE patients and the evaluation of ovarian reserve should be included in the patients' management in order to assess ovarian function. Moving from these premises, in the present study we demonstrated an impaired ovarian reserve in SLE patients in terms of AFC values and a negative correlation with hormonal and some demographic features. Disclosure of Interest: None declared